Eligibility for the Funding and Development from the German Federal Organizations in the Energy and Environmental Sector - Kutval, Ashish; Shafighi, Najla (Archives of Business Research, 2023)
The German government has set targets to increase renewable energy usage and decrease greenhouse gas emissions. They aim to raise the proportion of renewable energy in total energy consumption from 10.6% in 2010 to 17.1% by 2020. In 2022, the industrial sector accounted for over 44% of renewable energy usage, with a cost of around 17 billion euros. By 2030, the government expects renewable sources to contribute at least 65% of the national energy consumption. To encourage the growth of renewable energy, the government provides subsidies and grants through programs like KfW and the Federal Ministry BAFA. This thesis focuses on four research questions: the effectiveness of subsidies, optimizing technology support benefits, challenges faced by renewable energy businesses in accessing government support, and evaluating the impact of grant funding on the development of energy-efficient technology. Considering the specific needs of each company is crucial for making accurate investments.